Vegetation change over a period of 46 years in a Mediterranean mountain massif (Penyagolosa, Spain). Issue 4 (8th July 2020) - Merle, Hugo; Garmendia, Alfonso; Hernández, Héctor; Ferriol, María
Abstract: Questions: The Mediterranean mountain massifs are biodiversity hotspots threatened by climate change and land use transformations, among other factors. Did vegetation composition and α ‐ and β‐diversities change in mid‐ and high‐elevation Mediterranean ecosystems over the last 46 years? Can these changes be explained by climate change or land use? Location: Medium and high altitudes of the Penyagolosa Massif, Castellón, Eastern Spain. Methods: In 2014, we resurveyed 92 vegetation plots sampled in 1968, belonging to nine plant communities distributed on basic and acid soils. We performed estimates of α‐ and β‐diversity, multidimensional ordination of species composition, ecological characterisation of species and non‐parametric tests to identify vegetation change over time. Results: We observed different patterns of vegetation change depending on the plant community; an increase in α‐diversity, especially in high‐altitude habitats, and a homogenisation of species composition among plant communities. Seral communities and forests increased particularly in locations on basic soils that used to be occupied by pastures and communities of degraded successional stages. Higher Ellenberg indicator values of temperature and light, and loss of temperate taxa, which are usually rare in the region, were found in the climax forest of high altitudes and some acidophilous communities. However, altitudinal shifts of species distributions were detected only in 14% of plant species, both upwards and downwards. An increase of nitrophily at medium altitudes was also observed. Conclusions: The results suggested that land use change related with abandonment of agro‐sylvo‐pastoral systems was the major driving force of vegetation dynamics in most of the seral plant communities, while thermophilisation was more evident in the high‐altitude climax forest. Abstract : Very few studies have dealt with long‐term vegetation changes in Mediterranean mountains using floristic approaches. Here we resurveyed 92 relevés performed in 1968 in Penyagolosa (Spain), corresponding to plant communities that differ in altitude, soil type, and successional stage. Climate change and land use transformations are the main drivers of change, but with different effects depending on the plant community.